Empowerment of Women through Entrepreneurship in Gorkha District, Nepal - Koirala, Samjhana; Gyanwali, Shrijan; Ranabhat, Deepesh (INTELLIGENCE Journal of Multidisciplinary Research, 2024)
Promoting women’s empowerment through entrepreneurship and income-generating activities is a crucial factor in advancing the development of both families and society. This study investigates the impact of women's entrepreneurship on their empowerment, focusing on decision-making roles, reduced dependency, increased income levels, shifts in social perception, and employment generation in Gorkah District, Nepal. A sample of 150 women entrepreneurs was purposively selected for primary data collection, employing research-administered questionnaires. In this study, partial least squares structural equation modeling (PLS-SEM) was used to assess relationships between independent and dependent variables. The findings reveal that decision-making role, employment generation, and change in income levels significantly and positively influence women's empowerment, indicating that improvements in these areas are associated with increased women's empowerment. This research provides valuable insights for policymakers and practitioners and supports women’s entrepreneurship to promote women empowerment.